Kontribusi Loneliness Terhadap Perilaku Cybersex Pada Remaja - Putri Rezeki Aulia; Maya Yasmin (Populer: Jurnal Penelitian Mahasiswa, 2023)
This study aims to see the contribution of loneliness to cybersex behavior in adolescents. The hypothesis test used was simple linear regression analysis with 150 subjects aged 15-21 years, which were determined by snowball sampling technique. The measuring instruments used were the Cybersex Scale and the Loneliness Scale compiled by researchers based on aspects of Delmonico & Miller (2003) and Russell (1996). This study found that loneliness contributes significantly to cybersex with an R Square value of 0.090, which indicates that loneliness makes an effective contribution of 9% to cybersex behavior in adolescents.